An evaluation of tropical waves and wave forcing of the QBO in the QBOi models. (15th July 2020) - Holt, Laura A.; Lott, François; Garcia, Rolando R.; Kiladis, George N.; Cheng, Yuan‐Ming; Anstey, James A.; Braesicke, Peter; Bushell, Andrew C.; Butchart, Neal; Cagnazzo, Chiara; Chen, Chih‐Chieh; Chun, Hye‐Yeong; et al.
Abstract: We analyze the stratospheric waves in models participating in phase 1 of the Stratosphere–troposphere Processes And their Role in Climate (SPARC) Quasi‐Biennial Oscillation initiative (QBOi). All models have robust Kelvin and mixed Rossby‐gravity wave modes in winds and temperatures at 50 hPa and represent them better than most of the Coupled Model Intercomparison Project Phase 5 (CMIP5) models. There is still some spread among the models, especially concerning the mixed Rossby‐gravity waves. We attribute the variability in equatorial waves among the QBOi models in part to the varying horizontal and vertical resolutions, to systematic biases in zonal winds, and to the considerable variability in convectively coupled waves in the troposphere among the models: only roughly half of the QBOi models have realistic convectively coupled Kelvin waves and only a few models have convectively coupled mixed Rossby‐gravity waves. The models with stronger convectively coupled waves tend to produce larger zonal mean forcing due to resolved waves in the QBO region. Finally we evaluate the Eliassen–Palm (EP) flux and EP flux divergence of the resolved waves in the QBOi models. We find that there is a large spread in the forcing from resolved waves in the QBO region, and the resolved wave forcing has a robust correlation with model vertical resolution. Abstract : The QBOi models vary widely in their ability to simulate equatorial waves and in the magnitude of resolved wave‐forcing contributing to the driving of the model QBO. In the QBOi models, despite the varying set‐ups, vertical resolution emerged as a clear factor controlling the degree of wave forcing in the eastward QBO shear zones. This figure shows how the wave forcing due to resolved large‐scale eastward propagating waves relates to model vertical and horizontal resolution.